2008
DOI: 10.1080/13651500802095012
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression and their influence on the quality of life after total hip replacement: preliminary report

Abstract: Objective. The study investigated health-related quality of life in relation to mental status (anxiety and depression) and demographic factors in patients before and after total hip replacement due to osteoarthrosis. Methods. The SF-36, HADS, socio-demographic data questionnaire was delivered to a group of 184 subjects (108 females, 76 males) at the mean age at the time of surgery of 59 years. Questionnaires were delivered to the subjects 2 weeks before the surgery and 6 months after the operation (by mail). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…A total of 21 studies assessed depression or anxiety after TJR using a single-sample (TJR) repeated-measures design (pre-and post-surgery assessments; Attal et al, 2014;Badura-Brzoza et al, 2008;Cremeans-Smith et al, 2009;Dahlen, Zimmerman, & Barron, 2006;Davis et al, 2011;Duivenvoorden et al, 2013;Faller, Kirschner, & K€ onig, 2003;Hartley, Vance, Elliott, Cuckler, & Berry, 2008;Lopez-Olivio et al, 2011;McHugh, Campbell, & Luker, 2013;Montin et al, 2007;Papakostidou et al, 2012;Patel, Stygall, Harrington, Newman, & Haddad, 2010;Perez-Prieto et al, 2014;Pinto, McIntyre, Ferrero, Almeida, & Ara ujo-Soares, 2013;Rodriguez et al, 2005;Smith & Zautra, 2004;Stecz & Kocur, 2014b;Swinkels et al, 2009;Utrillas-Compaired, De la Torre-Escuredo, Tebar-Martinez, & Asunsolo-Del Barco, 2014). An additional four studies involved clinical trials where patients were randomly allocated into 'treatment' (experimental) and 'standard care' groups that were assessed pre-and post-surgery (Buker et al, 2014;Lin, 2011;Pellino et al, 2005).…”
Section: Research Designs and Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 21 studies assessed depression or anxiety after TJR using a single-sample (TJR) repeated-measures design (pre-and post-surgery assessments; Attal et al, 2014;Badura-Brzoza et al, 2008;Cremeans-Smith et al, 2009;Dahlen, Zimmerman, & Barron, 2006;Davis et al, 2011;Duivenvoorden et al, 2013;Faller, Kirschner, & K€ onig, 2003;Hartley, Vance, Elliott, Cuckler, & Berry, 2008;Lopez-Olivio et al, 2011;McHugh, Campbell, & Luker, 2013;Montin et al, 2007;Papakostidou et al, 2012;Patel, Stygall, Harrington, Newman, & Haddad, 2010;Perez-Prieto et al, 2014;Pinto, McIntyre, Ferrero, Almeida, & Ara ujo-Soares, 2013;Rodriguez et al, 2005;Smith & Zautra, 2004;Stecz & Kocur, 2014b;Swinkels et al, 2009;Utrillas-Compaired, De la Torre-Escuredo, Tebar-Martinez, & Asunsolo-Del Barco, 2014). An additional four studies involved clinical trials where patients were randomly allocated into 'treatment' (experimental) and 'standard care' groups that were assessed pre-and post-surgery (Buker et al, 2014;Lin, 2011;Pellino et al, 2005).…”
Section: Research Designs and Data Preparationmentioning
confidence: 99%
“…two studies byBadura-Brzoza et al (Badura-Brzoza et al, 2009;Badura-Brzoza et al, 2008),Orbell, Johnston, Rowley, Espley, & Davey, 1998), Davis et al (Davis et al, 2009; Davis et al, 2011), Stecz & Kocur (Stecz & Kocur, 2014a, 2014b), Salazar et al (Salazar et al, 2011; Salazar et al, 2014), and Swinkels et al (Swinkels & Allain, 2013; Swinkels et al, 2009); (2) five studies by Pinto et al (Pinto, McIntyre, Araujo-Soares, Ferro, & Almeida, 2014; Pinto, McIntyre, Araujo-Soares, Costa, & Almeida, 2014; Pinto, McIntyre, Ferrero, Almeida, & Araujo-Soares, 2013; Pinto, McIntyre, Ferrero, Almeida, & Ara ujo-Soares, 2013; Pinto, McIntyre, Ferrero, Araujo-Soares, & Almeida, 2013), and (3) one set of three studies by CreameansÀSmith/Pinna et al (Cremeans-Smith, Greene, & Delahanty, 2011; Cremeans-Smith, Soehlen, Greene, Alexander, & Delahanty, 2009;…”
mentioning
confidence: 99%
“…Although only prospective studies can potentially clarify this issue, anxiety can foster injury (Lavallee and Flint, 1996), and injury can lead to osteoarthritic joint damage. Especially in the context of total hip replacement for severe hip osteoarthritis where many candidates have previously fallen and fractured their hips, it seems patients who demonstrate declining, rather than improved functional ability following this procedure, may do so as a result of factors related to their mental health status, rather than their physical status (Badura-Brzoza et al, 2008). In this regard, Rolfson et al (2009) found pre-operative anxiety/depression was a strong predictor of pain relief and patient satisfaction, in that those who were less anxious had less pain and were more satisfied with the surgical procedure and its outcome.…”
Section: Key Research Findingsmentioning
confidence: 99%
“…This link between anxiety, pain, and disability in people with osteoarthritis, which was also observed by Marks (2007) in almost 9.5% of end-stage hip osteoarthritis cases suggests ample numbers of adults with disabling osteoarthritis may have mood and/or anxiety disorder histories that may often go undetected or overlooked in the treatment schedule being offered. An equal number may exhibit prevailing symptoms of emotional distress that may occur simultaneously or independently, either before or after surgery, or both, as well, and this can magnify pre-operative osteoarthritis disability and slow the postoperative recovery process (Badura-Brzoza et al, 2008), thus strengthening the case for preventing and treating anxiety in adults with osteoarthritis at all disease stages. Indeed, even though surgery for osteoarthritis is usually successful, it has been observed that even the presence of moderate trait anxiety can significantly impair the hip osteoarthritis surgical candidates health quality of life both before, as well as after surgery (Montin et al, 2007), even though this is often believed to return the patient to optimal function.…”
Section: Implications Of Anxiety In the Context Of Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation